Mediating role of attitude, behavioral control, and stakeholders' support on the relationship between entrepreneurial skills and entrepreneurial intentions of it employees in Pakistan - Shabbir, Muhammad Salman (2017)
Pakistan being a developing country has a high rate of unemployment among young population. This present study examines the effects of entrepreneurial skills on developing entrepreneurial intentions of IT employee of Punjab, Pakistan. The study also examines the mediating role of attitude towards behavior, perceived behavioral control, and stakeholders’ support system in the relationship between entrepreneurial skills and entrepreneurial intentions. The probing into the literature of concepts and conceptualizations of the theories permitted a theoretical framework that identified the research issues and the research gap. The data were collected from IT employees working with SECP registered companies in Punjab, Pakistan using a cross-sectional study design. The study used simple random sampling technique to the selected 398 employees working with Information Technology (IT) companies in Punjab, Pakistan. For the initial data screening SPSS 20 was used, and then the Partial Least Squares Structural Equation Modelling (PLS-SEM) was employed to test the present study hypotheses. This study found the significant mediating effects of attitude towards behavior, perceived behavioral control, and stakeholders’ support system on the relationship between EPS, LS, MS, PMS, and TS and entrepreneurial intentions of IT employees in Punjab, Pakistan. The findings of this study further reveal that entrepreneurial intentions depend on the degree of EPS, LS, MS, PMS, and TS. The results of this study provide important insights to the policy making institutions, government, and the researchers to further understand the effects of entrepreneurial skills on developing entrepreneurial intentions and mediating role of attitude towards behavior, perceived behavioral control, and stakeholders’ support system. The findings of this research extended to the body of knowledge on entrepreneurial skills and entrepreneurial intentions in Pakistani context.